Perencanaan Perbaikan Proses pada Produksi Genteng dengan Metode Six Sigma - Dwi Iryaning Handayani (Jurnal Teknik Industri, 2009)
UD. BJ Mendit on Mendit Barat, Kec. Pakis is one of centrale of home industry in Malang with it's roof production process. From the observation that the researcher do into UD. BJ Mendit, finded that the production process had been doing often with technical and non technical problems that make some failed roof product with the criterion are keropos, break, barst, gopel, sandbank. Way of this roof production planning repair is important to do so that can make this production unit produce an unfailed product and reduce loss. Purposes of this research are identifying types of roof failed product, analysing main cause of roof failed product with FMEA, and giving recommended action for Mendit's roof production process repair. This research doing the same steps as same as Six Sigma cycle: DMAIC, but not doing the last step, Control. On Define step, are doing product identifying and make the Six Sigma team. On Measure step, are determining priority failed product identifying into CTQ (Critical To Quality) and measurement of present performance with counting the DPMO (Defect Per Million Opportunities) dan Sigma level. On Analyze step, is detecting main atributs that influencing the failed product on CTQ. On Improve step, is doing process improvement with developing alternative to reduce failed product atributs. From the steps had done, finded that the biggest failed criterion is keropos. Keropos is caused by lack of skill and correctness of worker on processing the raw material, can also caused by process execution which not fully corret so that produce critical process to be repaired first to increase the quality of Mendit's roof.